Total Eclipses of the Sun : Expanded Edition - Zirker, Jack B. (Book collections on Project MUSE., 2014)
Eclipses have captured attention and sparked curiosity about the cosmos since the first appearance of humankind. Having been blamed for everything from natural disasters to the fall of kings, they are now invaluable tools for understanding many celestial as well as terrestrial phenomena. This clear, easy-to-understand guide explains what causes total eclipses and how they can be used in experiments to examine everything from the dust between the planets to general relativity. A new chapter has been added on the eclipse of July 11, 1991 (the great Hawaiian eclipse). Originally publishe.